RESOURCE SHARING IN RAJASTHAN GOVERNMENT ENGINEERING INSTITUTION LIBRARIES DESIGNING A COMPREHENSIVE MODAL - Gopal Krishna Jha (International Journal of Multidisciplinary Research and Studies, 2021)
It is common knowledge that libraries are the pillars of support for every given institution or organization to which they are connected. They are obligated to furnish their consumers with timely information that is pertinent to their needs. The information and communication technology of today has an effect on many facets of human life. The use of information and communication technology, abbreviated as ICT, is becoming increasingly widespread across all types of libraries (Dhimna, 2001; Dhiman, 2003). As a result, the function of information professionals has shifted toward an emphasis on the comprehension and effective utilization of technology resources in order to satisfy the growing demand on information that the society exhibits. This calls for an accurate understanding of the influence that technology has had on the notion of libraries and the services they provide (Shrivastava, 2007). Because of the massive amounts of publications and interdisciplinary researches that are being enuraged at the level of higher education, the information needs of the users of libraries — whether they are academic colleges or the engineering colleges — have also become complex and problematic. This is the case regardless of whether the colleges in question are academic or engineering. The academic staff and students at these institutions deserve nothing less than the maximum satisfaction, which is why the librarians who work in these institutions need to devote their full attention to the task of acquiring relevant and necessary literature in these fields. In this precarious circumstance, librarians should have a crystal clear understanding of both the information-seeking behaviour of their users as well as the information-seeking needs of their users. This will allow the libraries to not only meet the information-seeking needs of their users but also improve the services that are already provided.